Biosonar emission characteristics and beam control of odontocetes - Song, Zhongchang; Zhang, Yu; Wei, Chong; Yang, Wuyi; Xu, Xiaohui (Science Press, 2020)
Odontocetes have evolved for millions of years to own a unique echolocation system. The exceptional performance of odontocetes echolocation system can provide reference to artificial sonar systems, acoustic metamaterials and sound control designs. Research on odontocetes biosonar requires interdisciplinary effort, including acoustics, biology, biomimetics, anatomy, physiology and signal analysis. In this paper, we review odontoctes’ biosonar emission process from aspects of anatomy, biosonar signal and beam formation. To begin, computed tomography scanning and untrasound measurements are combined to reconstruct the sound speed and density distributions. To follow, efforts are thrown to probe into the biosonar signal and its corresponding acoustic behavior. Numerical simulations are used to investigate the odontocetes’ biosonar beam formation. The secret of exceptional performance of odontocetes’ echolocation system lies in their unique anatomy. Odontocete integrates acoustic structures with different acoustic impedances, namely solid bony structures, air space and soft tissues as a whole emission system to efficiently modulate sound propagation and sound beam formation. These acoustic structures are well organized in the forehead, forming a natural acoustic metamaterial to perform a good control of sounds. These results can enlighten artificial sonar designs.